Risk Factors for Patellar Clunk or Crepitation after Primary Total Knee Arthroplasty: A Systematic Review and Meta-analysis - Duan, Guman; Cai, Sijia; Lin, Weiwei; Pan, Yongwei (The Journal of Knee Surgery, 2020)
Patellar clunk and crepitation (PCC) have been reported as a consequence of primary total knee arthroplasty (TKA). The incidence and contributing factors have not been fully defined. We performed this systematic review to evaluate factors associated with PCC following primary TKA. We identified studies on PCC following TKA from an electronic search of articles in Medline, Embase and the Cochrane databases (dated up to May 2018). Eighteen studies altogether, including 600 cases of PCC within 8,131 TKAs, were included in the meta-analysis. Several factors including demographic, intraoperative, clinical variables, and radiographic measurements were pooled for meta-analysis. Among intraoperative and clinical variables, patients involved with patellar retention (odds ratio [OR] = 9.420; confidence interval [CI]: 5.770–13.070), lateral reticular release (OR = 2.818; CI: 1.114–7.125), and previous surgery (OR = 2.724; CI: 1.549–4.790) were more likely to having PCCs. Among radiographic measurements, increased anterior tibial offset (weighted mean difference [WMD] = 0.387; CI: 0.139–0.634), increased joint line changes (WMD = 1.325; CI: 0.595–2.055), and increased knee flexion angle (WMD = 3.592; CI: 1.811–5.374) were considered risk factors associated with PCC. Demographic factors (age, gender, body mass index [BMI], and diagnosis) and other reported radiographic measurements were not associated with PCCs. This study identified intraoperative variables (patellar retention and lateral reticular release), clinical variables (previous surgery), and radiographic measurements (increased anterior tibial offset, increased joint line changes, and increased postoperative knee flexion angle) that contribute to an increased risk for PCC. Modifiable factors (patellar retention and lateral reticular release) should be considered and addressed to limit the risk for PCC following TKA. Patients with conditions that may not be modifiable may benefit from counseling about their increased risks for PCC to limit potential dissatisfaction with their procedure.
Keywords: risk factors; patellar crepitus; patellar clunk; total knee arthroplasty; meta-analysis